Prion Protein Misfolding - Kupfer, L (Bentham Science Publishers Ltd., 2009)
The crucial event in the development of transmissible spongiform encephalopathies (TSEs) is the conformational change of a host-encoded membrane protein - the cellular PrP(C) - into a disease associated, fibril-forming isoform PrP(Sc). This conformational transition from the α-helix-rich cellular form into the mainly β-sheet containing counterpart initiates an ‘autocatalytic’ reaction which leads to the accumulation of amyloid fibrils in the central nervous system (CNS) and to neurodegeneration, a hallmark of TSEs. The exact molecular mechanisms which lead to the conformational change are still unknown. It also remains to be brought to light how a polypeptide chain can adopt at least two stable conformations. This review focuses on structural aspects of the prion protein with regard to protein-protein interactions and the initiation of prion protein misfolding. It therefore highlights parts of the protein which might play a notable role in the conformational transition from PrP(C) to PrP(Sc) and consequently in inducing a fatal chain reaction of protein misfolding. Furthermore, features of different proteins, which are able to adopt insoluble fibrillar states under certain circumstances, are compared to PrP in an attempt to understand the unique characteristics of prion diseases.